LOGISTICS INDUSTRY OF UKRAINE: ECONOMIC SIGNIFICANCE OF THE INDUSTRY, LOSSES AND DEVELOPMENT PROSPECTS IN THE CONDITIONS OF WAR (Development Service Industry Management, 2023)
The market of logistics services plays an important role in the economy of Ukraine. Logistics is the blood system of the country's economy, a set of operations that are carried out with the aim of delivering the product to the consumer. This article is devoted to the issues of determining the role of the logistics sector in the creation of the gross domestic product of the national economy of Ukraine. The specific weight of transport, warehousing, postal and courier activities in the structure of the gross domestic product of Ukraine has been determined. It has been noted that there are opportunities for the growth of the indicator of the specific weight of the logistics industry in the GDP of Ukraine, comparing this indicator with the indicators of other countries. An analysis of Ukraine's export-import operations in dynamics has been carried out; a negative trend of a decrease in product exports and an increase in the negative balance has been noted. The structure of export and import by types of transport in terms of value and physical has been studied. It has been confirmed that the logistics sphere is one of the important components of the development of the national economy of Ukraine, which depends on the development of the entire economy of the country, a scientific approach to further effective development. Losses of aviation, water, road, railway and warehouse infrastructure of Ukraine caused by military actions have been determined. The main prospects for the future development of the transport and warehousing sector of the economy have been outlined. It has been found out that the prospects for the development of the logistics services market in Ukraine directly depend on the timing of the end of the war, as a result of which there is an objective need to quickly rebuild the logistics system, form new cargo delivery chains, change the direction of trade flows due to the blockade of Ukrainian seaports and the partial loss of railway network.
Keywords: logistics; logistics infrastructure; export; import; gross domestic product; water transport; railway transport; air transport; road transport; warehouse logistics; war; losses from war; Eurorail; warehouse; postal and courier activity